Evaluation of fluorimetric assay conditions for measuring leucine aminopeptidase activity in soils - Qingqing He; Shunyu Huang; Jipeng Wang (PLoS ONE, 2026)
Leucine aminopeptidase (LAP) plays a crucial role in the hydrolysis of proteinaceous nitrogen in soils. However, existing studies use varying conditions in the fluorimetric assay of soil LAP, which hinders cross-study comparison of the measured activities. Using one purified enzyme and three soils of contrasting properties, we examined how LAP activity responded to variations in assay conditions including buffer pH, substrate (L-leucine-7-amido-4-methylcoumarin) concentration, temperature, incubation time, soil amount, and metal ion concentrations. We found that: (1) the optimal pH for LAP activity ranged from 7 to 9; (2) a substrate concentration of 250 μM was necessary to achieve zero-order reaction kinetics; (3) LAP activity increased as the temperature rose from 10 to 40 °C, with a Q 10 value between 1.63 and 2.45; (4) the rate of the enzymatic reaction remained stable for at least 3 hours; (5) measured activity decreased as the amount of soil used for homogenate preparation increased from 0.5 to 2.0 g; and (6) the activity of LAP was not substantially stimulated by the addition of metal ions, suggesting that a metal cofactor is not needed for the fluorimetric assay of LAP. We also compared the behaviors of LAP with those of the colorimetrically measured arylamidase that catalyze the release of an N-terminal amino acid from peptides, amides, or arylamides, and found that they may represent the same group of soil enzymes. Our findings may help standardize the assay protocol for soil LAP, which is essential for conducting meta-analysis of enzyme activities measured across different studies.